Constitutional Identity - Mathieu, Bertrand (International Law From A Central European Perspective, 2022)
Constitutional identity corresponds to the essential elements of national identity that a people has decided to enshrine in its Constitution, thus giving them legal effect. National identity is what allows a political community to be identified. This State formed by a People and endowed with the attribute of sovereignty is defined by its history, its values… so many elements that characterize both its raison d’être and its specificity. It is at the same time an element of separation from what is not it, an element of dialogue with other communities based on other principles of identity, an element of sharing with other States having in common some of these values. In a context where globalization is tending to erase these identity values, the resurgence of national identity must lead us to question both its nature and its place in the international and more particularly supranational legal order. It is in fact an instrument of both cooperation and resistance. Indeed, European legal systems, built on the will to promote and defend shared values, are now tending to legally impose a common identity, exclusive of national identities, based on principles that appear to be consensual but whose substantial definition, essentially produced by jurisdictional bodies, tends to achieve a European imperium that is not devoid of ideological connotations. The resistance of a number of national jurisdictions, in various forms, to this imperium makes it necessary to seek mechanisms that allow both the promotion of common values and the protection of identity-based values. These mechanisms must restore the place of political power which, in a democracy, is the most legitimate to settle possible conflicts. The determination of new mechanisms for regulating the balance between the requirements of national identities and those linked to the values and principles that sovereign States have decided to put in common will probably determine the survival of European legal systems. KEYWORDS: identity, Council of Europe, nation, European Union, values